2019
DOI: 10.1136/bmjopen-2018-024351
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and psychosocial interventions offered to forensic mental health inpatients: a systematic review

Abstract: ObjectiveTo examine the evidence for the use of psychological and psychosocial interventions offered to forensic mental health inpatients.DesignCINAHL, MEDLINE, PsycINFO, ScienceDirect and Web of Science databases were searched for research published in English between 1 January 1990 and 31 May 2018.Outcome measuresDisturbance, mental well-being, quality of life, recovery, violence/risk, satisfaction, seclusion, symptoms, therapeutic relationship and ward environment. There were no limits on the length of foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 38 publications
0
32
0
1
Order By: Relevance
“…If the opportunity to participate in research is an ethical right (4), it seems FMHS patients are seldom granted this right. Research pertaining to core interventions is lacking on a broad scale (22,23). In an analysis of available systematic reviews, Howner et al (22) concluded that none of the broad range of intervention categories they investigated had a sufficient evidence base in FMHS settings.…”
Section: Introductionmentioning
confidence: 99%
“…If the opportunity to participate in research is an ethical right (4), it seems FMHS patients are seldom granted this right. Research pertaining to core interventions is lacking on a broad scale (22,23). In an analysis of available systematic reviews, Howner et al (22) concluded that none of the broad range of intervention categories they investigated had a sufficient evidence base in FMHS settings.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review (2019) of randomised controlled trials (RCT) of psychological interventions offered to forensic/secure mental health inpatients (n = 9 studies including 523 participants) reported that current practice is based on limited evidence with no consistent significant findings [17]. Study sample sizes ranged from 14 to 112.…”
Section: Introductionmentioning
confidence: 99%
“…Economic evaluations were not included in the studies. The review concluded that further studies are needed to clarify the evidence base [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to achieve the necessary balance between risk management and strength enhancement as prescribed by GLM, both internal capabilities and external conditions must be developed throughout the rehabilitative process. In terms of internal capabilities, various interventions already in established use in forensic psychiatry can be used in a targeted and individual manner (47)(48)(49). CBT based approaches, group and individual, focusing on problem-solving and interpersonal skills, have the best evidence base for the treatment of forensic patients and should be preferred to other models (1).…”
Section: Discussionmentioning
confidence: 99%